Palladium-Catalyzed Synthesis of Pyrayaquinones, Murrayaquinones, and Murrayafoline-B - Kutz, Sebastian K.; Schmidt, Arndt W.; Knölker, Hans-Joachim (Synthesis, 2017)
We describe the total synthesis of murrayafoline-B and seven carbazole-1,4-quinone alkaloids. A palladium(II)-catalyzed oxidative cyclization is used to construct the carbazole skeleton. Pyran annulation and oxidation provide pyrayaquinone-A, -B, and -C. DIBAL-H-promoted reductive ring opening of pyrano[3,2-a]carbazole precursors leads to the prenylated and geranylated carbazole-1,4-quinone alkaloids murrayaquinone-B, -C, -D, and -E and to murrayafoline-B.
Keywords: carbazole; alkaloids; quinones; natural products; total synthesis; palladium; Frémy’s salt; ring opening